Food safety trends: From globalization of whole genome sequencing to application of new tools to prevent foodborne diseases. (November 2016) - Wang, Siyun; Weller, Daniel; Falardeau, Justin; Strawn, Laura K.; Mardones, Fernando O.; Adell, Aiko D.; Moreno Switt, Andrea I.
Abstract: Background: Food safety is a priority for all stakeholders associated with the food supply and consumption. Outbreaks and recalls caused by microbial pathogens are widely attributed to contaminated foods, and lead to considerable public health and economic burdens. Scope and approarch: This review presented major current trends in food safety research, regulation and strategic development. Specifically we discussed about: (i) worldwide application of genomic data in foodborne pathogen surveillance and outbreak investigation; (ii) Geographic Information Systems (GIS) in food safety to prevent and predict pathogen contamination; (iii) modeling tools adapted from landscape ecology, network analysis and niche modeling to prevent foodborne diseases; and (iv) meta-analysis of food safety data to facilitate decision making. Key findings and conclusions: While some of these technologies are receiving increasing recognition around the world (e.g., WGS), others are still at their infancy in regards to their application in food safety (e.g., meta-analysis). The establishment of relevant, valid and multi-dimensional databases is the key to effective application of many new trends in food safety described in this review. Highlights: Whole genome sequencing (WGS) is acquiring global importance in food safety. Application of WGS in developing countries is a reality. Tools from epidemiology are promising tools to be applied in food safety. Meta-analyses are necessary to translate science to decision making.